Disminución de los costos de producción de conservas de atún optimizando el uso de vapor - Jiménez Bellasmil, Juan (2015)
The present study was aimed to obtain energy saving in the sterilization step in the processing of canned tuna by recovering condensate. The data were obtained from the company "Conservera de las Américas” and to implement the energy balance an experimental module consist of an experimental flash vessel 2 L of capacity built in stainless steel AISI 304 L was used also an electric boiler of 7,5 kw and a condenser of hull and tubes type made of stainless steel AISI 304 L. The total energy required for the canned fish was 211,58 kcal/kg; determining a thermal efficiency of 90 %. The recovery of condensate at high pressure as flash steam from the sterilizer to preheat the water supply to the boiler increased their efficiency in 4 %. The heat-recovery system requires a heat exchanger tubes and hull built in carbon steel with an overall heat transfer coefficient of 1095 kcal/h m2 ºC. The costs of production decreased by recovering the energy of the steam condensate through flash steam preheating the water supply to the boiler, obtaining a fuel savings of 51840gal/1000 BHP year corresponding to S/ 192 471.55 /1000 BHP year.